Repeated loading of soil containing granulated rubber and multiple geocell layers - Tafreshi, S.N. Moghaddas; Khalaj, Omid; Dawson, Andrew (Elsevier, 2014)
Sandy soil/aggregate, such as might be required in a pavement foundation over a soft area, was treated by the addition of one or more geocell layers and granulated rubber. It was then subjected to cyclic loading by a 300 mm diameter plate simulative of vehicle passes. After an initial study (that established both the optimum depth of the uppermost geocell layer and of the geocell inter-layer spacing should be 0.2 times plate diameter), repeated loading was applied to installations in which the number of geocell layers and the presence or absence of shredded rubber layers in the backfill was changed. The results of the testing reveal the ability of the composite geocell-rubber-soil systems to ‘shakedown’ to a fully resilient behavior after a period of plastic deformation except when there is little or no reinforcement and the applied repeated stresses are large. When shakedown response is observed, then both the accumulated plastic deformation prior to a steady-state response being obtained and the resilient deformations thereafter are reduced. Efficiency of reinforcement is shown to decrease with number of reinforcement layers for all applied stress levels and number of cycles of applied loading. The use of granulated rubber layers are shown to reduce the plastic deformations and to increase the resilient displacements compared to the comparable non-rubber construction. By optimal use of geocells and granulated rubber, deformations can be reduced by 60–70% compared with the unreinforced case while stresses in the foundation soil are spread much more effectively. On the basis of the study, the concept of combining several geocell layers with shredded rubber reinforcement is recommended for larger scale trials and for economic study.